THE UK'S EXPERIENCE IN INTERNATIONAL TOURISM DEVELOPMENT: CHALLENGES, OPPORTUNITIES AND ADAPTATION FOR UKRAINE (Development Service Industry Management, 2025)
The article defines the concept of "international tourist services market" as a set of international organizational and economic relations between tourism entities that provide services on the world market in the formation, sale and consumption of tourist services, which are intended to satisfy a wide range of physiological, material and spiritual needs of tourists on an international scale. The United Kingdom of Great Britain and Northern Ireland is characterized as a popular tourist destination. It is established that the United Kingdom as a national brand ranks 5th in the world ranking of attractiveness for tourists, and 8th in the world in terms of the number of visits by international tourists. It is proven that the consequences of Brexit for the tourism industry of Great Britain directly depend on the conditions of exit from the EU. Exit without an agreement will cause huge losses to the entire tourism sector and will lead to a sharp increase in the cost of tourist services. Today, one of the promising directions for resolving this issue is to provide a political and economic Roadmap for the further development of the tourism industry in the context of Brexit and to preserve most of the existing agreements in the field of tourism of the United Kingdom with the EU countries in order to implement a competent tourism policy and obtain certain economic benefits. It has been determined that concluding an agreement and ensuring acceptable conditions for leaving the EU is the primary task of the UK Government in the further development of the tourism industry. It was found that today the country's international tourism policy is characterized by the following problematic aspects: insufficient level of competitiveness of the image of Great Britain among competing countries; low level of representativeness of Great Britain as the best tourist destination in foreign advertising materials; the presence of gaps in the "packaging" (presentation and delivery) of tourist services to foreign tourists; low level of throughput of current airports in Great Britain. The current problems and prospects for the development of the international tourism market of Great Britain in the context of sustainable development are outlined. It has been established that the main trends are: ensuring environmental protection in the country and focusing state policy in the field of tourism on the development of ecological tourism; activating the development of tourism in rural areas; promoting the purchase of local products by tourists from Great Britain; organizing tourist programs for international tourists with scientific and educational purposes; using public transport and/or electric vehicles when traveling in Great Britain. The experience of the United Kingdom has been analyzed in terms of its potential value for Ukraine in the process of shaping its own tourism policy and model for the development of the tourism industry in the context of post-war reconstruction and integration into the global tourism space. It has been determined that the British experience of sustainable and innovative approaches to tourism development can serve as a benchmark for enhancing the competitiveness of the Ukrainian tourism market and for forming a safe and attractive image of the country at the international level.
Keywords: tourism; tourist service; international tourist services market; Great Britain; tourist destination